New species and taxonomic notes on the Apatelodidae (Lepidoptera: Bombycoidea) - Orlandin, Elton; Piovesan, Mônica; Carneiro, Eduardo (Zootaxa, 2025)
In recent years, the description of new species of Apatelodidae has increased significantly, including details on the morphology of immature stages and their natural history. Recently, a new phylogenetic classification of Apatelodidae genera was proposed resulting in the addition of 16 new genera. During that study, several dissected specimens exhibited characteristics that made them strong candidates for new species. Here, we describe six of these new species: Drepatelodes cabore Orlandin & Carneiro sp. nov., Drepatelodes chicomendes Orlandin & Piovesan sp. nov., Drepatelodes karusakaibu Orlandin & Piovesan sp. nov., Drepatelodes manaos Orlandin & Piovesan sp. nov., Tamphana ajuricaba Orlandin & Piovesan sp. nov., and Tuyvae guyranhandu Orlandin, Piovesan & Carneiro sp. nov. Additionally, we take this opportunity to propose three new names for three homonymic genera: Aymarodes Orlandin, Piovesan & Carneiro nom. nov., Lempirodes Orlandin, Piovesan & Carneiro nom. nov., and Zapatodes Orlandin, Piovesan & Carneiro nom. nov.